COMO AS FORMAS E FERRAMENTAS DE TRANSFERÊNCIA DE CONHECIMENTO PODEM AGREGAR VALOR NA GESTÃO DE PROJETOS: UM ESTUDO DE CASO. - Silva, Alessandra Karine Figueiredo (2007)
The main objective of this work is to identify how the forms and tools of knowledge transference can add value to knowledge management to a company of the sector of telecommunications. The research is based on knowledge management practices and project management. The research adopts a structured questionnaire and a statistical treatment of data raised, based on Harold Kerzner model, which is called PMMM (Project Management Maturity Model). The work results showed that the researched company needs to recognize the necessity of the project management, its benefits and its applicability and also need to use the techniques and instruments of knowledge management that add value to the project management, to increase its efficiency and effectiveness in the project management.